2022
DOI: 10.1002/cssc.202200594
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Optimization of Charge Separating Dyes for Solar Energy Conversion

Abstract: Dye‐sensitized photoelectrochemical cells are promising devices in solar energy conversion. However, several limitations still have to be addressed, such as the major loss pathway through charge recombination at the dye‐semiconductor interface. Charge separating dyes constructed as push‐pull systems can increase the spatial separation of electron and hole, decreasing the recombination rate. Here, a family of dyes, consisting of polyphenylamine donors, fluorene bridges, and perylene monoimide acceptors, was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…A semiempirical quantum classical approach has been used to model the electron injection from the photoexcited BODIPY dyes into TiO 2 . This approach, which is a combination of quantum dynamics based on an Extended Hückel Hamiltonian for the photoexcited electron and a priori generated nuclear trajectories obtained by using semiempirical molecular dynamics, permits the simulation of photoinduced electron injection in extended systems, taking nuclear dynamics into account. It has previously successfully been applied to model electron injection from NDI based dyes into TiO 2 as well as charge separation in push–pull dyes. , Structure optimization and nuclear dynamics were performed using the DFTB+ program (version 22.2), with GFN-1xTB as electronic structure method . Detailed information on the construction of the simulation box and computational settings can be found in the Supporting Information.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A semiempirical quantum classical approach has been used to model the electron injection from the photoexcited BODIPY dyes into TiO 2 . This approach, which is a combination of quantum dynamics based on an Extended Hückel Hamiltonian for the photoexcited electron and a priori generated nuclear trajectories obtained by using semiempirical molecular dynamics, permits the simulation of photoinduced electron injection in extended systems, taking nuclear dynamics into account. It has previously successfully been applied to model electron injection from NDI based dyes into TiO 2 as well as charge separation in push–pull dyes. , Structure optimization and nuclear dynamics were performed using the DFTB+ program (version 22.2), with GFN-1xTB as electronic structure method . Detailed information on the construction of the simulation box and computational settings can be found in the Supporting Information.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These studies were predominantly performed in the frame of redox cascades in biology and in solar energy conversion. [25][26][27][28][29][30][31][32][33][34][35] In the current contribution, we follow our recently introduced protocol to assess the thermodynamics and kinetics of intramolecular charge transfer processes along efficient reaction coordinates within the Marcus picture [36][37][38][39] as well by means of dissipative quantum dynamics. [40,41] The molecular model systems are built in a modular approach and consist of an oligo-thiophene decorated by one or two TEMPO units as well as a linker connecting the backbone and the redox-active centers chemically.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, several theoretical as well as joint theoretical‐experimental studies can be found that focus on the comparison of calculated charge transfer rate constants obtained using semi‐classical Marcus theory and molecular dynamical (MD) simulations. These studies were predominantly performed in the frame of redox cascades in biology and in solar energy conversion [25–35] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation